Predicting pathological outcomes in patients undergoing robot‐assisted radical prostatectomy for high‐risk prostate cancer: a preoperative nomogram. (11th May 2015) - Abdollah, Firas; Klett, Dane E.; Sood, Akshay; Sammon, Jesse D.; Pucheril, Daniel; Dalela, Deepansh; Diaz, Mireya; Peabody, James O.; Trinh, Quoc‐Dien; Menon, Mani
<x xml:space="preserve">Abstract</x> Objective To identify which high‐risk patients with prostate cancer may harbour favourable pathological outcomes at radical prostatectomy (RP). Patients and methods We evaluated 810 patients with high‐risk prostate cancer, defined as having one or more of the following: PSA level of >20 ng/mL, Gleason score ≥8, clinical stage ≥T2c. Patients underwent robot‐assisted RP (RARP) with pelvic lymph node dissection, between 2003 and 2012, in one centre. Only 1.6% (13/810) of patients received any adjuvant treatment. Favourable pathological outcome was defined as specimen‐confined disease (SCD; pT2–T3a, node negative, and negative surgical margins) at RARP‐specimen. Logistic regression models were used to test the relationship among all available predicators and harbouring SCD. A logistic regression coefficient‐based nomogram was constructed and internally validated using 200 bootstrap resamples. Kaplan–Meier method estimated biochemical recurrence (BCR)‐free and cancer‐specific mortality (CSM)‐free survival rates, after stratification according to pathological disease status. Results Overall, 55.2% patients harboured SCD at RARP. At multivariable analysis, PSA level, clinical stage, primary/secondary Gleason scores, and maximum percentage tumour quartiles were all independent predictors of SCD (all P < 0.04). A nomogram based on these variables showed 76% discrimination accuracy in predicting SCD, and very favourable calibration characteristics. Patients with SCD had significantly higher 8‐year BCR‐ (72.7% vs 31.7%, P < 0.001) and CSM‐free survival rates (100% vs 86.9%, P < 0.001) than patients with non‐SCD. Conclusions We developed a novel nomogram predicting SCD at RARP. Patients with SCD achieved favourable long‐term BCR‐ and CSM‐free survival rates after RARP. The nomogram may be used to support clinical decision‐making, and aid in selection of patients with high‐risk prostate cancer most likely to benefit from RARP.